2016
DOI: 10.1002/polb.24067
|View full text |Cite
|
Sign up to set email alerts
|

4‐hydroxythiophenol grafted PS‐b‐PAA block copolymers: Preparation and formation of porous and bowl‐shaped assemblies

Abstract: 4-Hydroxythiophenol (HTP) grafted poly(styrene-bacrylic acid) (PS-b-PAA) block copolymers (BCPs) (PS-b-PAA-g-HTP) was synthesized using the esterification reaction between the carboxyl groups and hydroxyl groups. Self-assembly behavior of the graft copolymer in 1,4-dioxane/water was investigated. Assemblies of different morphologies, porous, and bowl-shaped structures, could be easily prepared. A possible mechanism for the formation of the porous and bowlshaped structures was discussed. The present study showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…PS- b -PAA- g -HFD was prepared by the esterification reaction between PS- b -PAA and HFD with the catalysis of 4-( N , N -dimethylamino)­pyridinium-4- p -toluenesulfonate (DPTS), which was synthesized according to the previous work . The mixture of PS- b -PAA/1,4-dioxane solution (10.0 mL, 5.0 mg/mL) and CH 2 Cl 2 (10.0 mL) was added to a round-bottomed flask at room temperature under a nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PS- b -PAA- g -HFD was prepared by the esterification reaction between PS- b -PAA and HFD with the catalysis of 4-( N , N -dimethylamino)­pyridinium-4- p -toluenesulfonate (DPTS), which was synthesized according to the previous work . The mixture of PS- b -PAA/1,4-dioxane solution (10.0 mL, 5.0 mg/mL) and CH 2 Cl 2 (10.0 mL) was added to a round-bottomed flask at room temperature under a nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…PS-b-PAA-g-HFD was prepared by the esterification reaction between PS-b-PAA and HFD with the catalysis of 4-(N,N-dimethylamino)pyridinium-4-p-toluenesulfonate (DPTS), which was synthesized according to the previous work. 31 The mixture of PS-b-PAA/1,4-dioxane solution (10.0 mL, 5.0 mg/mL) and CH 2 Cl 2 (10.0 mL) was added to a round-bottomed flask at room temperature under a nitrogen atmosphere. The DIPC/CH 2 Cl 2 (5.49 × 10 −4 mol) and DPTS (5.49 × 10 −4 mol) were introduced to the above mixture dropwise (∼100 μL/min), and the solution was stirred for 40 min at room temperature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[28,40,85] Moreover, there are also studies to explain the formation mechanism of BNPs from the perspective of phase separation. [18,37,79,82,100] Recently, our group monitored the formation process of BNPs self-assembled from amphiphilic homopolymers and proposed a comprehensive mechanism involving the additional viscosity, chain mobility and phase separation. [30] It was found that porous spheres (spheres filled with bubbles) were the intermediates of BNPs.…”
Section: Self-assembly Of Amphiphilic Moleculesmentioning
confidence: 99%
“…Besides, the PLA phase could be selectively degraded under simulated physiological condition. Li and coworkers [ 79 ] synthesized 4‐hydroxythiophenol (HTP) grafted poly(styrene‐ b ‐acrylic acid) (PS‐ b ‐PAA) block copolymers. The additional viscosity provided by HTP during self‐assembly led to the formation of bowl‐shaped and porous nanoparticles at very low initial concentrations of the polymer, for example, 0.01 and 0.02 wt%, respectively.…”
Section: Design Strategies Preparations and Mechanisms Of Bnpsmentioning
confidence: 99%